UAV based survey on portions of the Crocodile, Sabie, and Olifants rivers at Kruger National Park, Limpopo, South Africa to obtain LiDAR, RGB and multispectral imagery - Graham, P. M.; Pike, T.; Pattinson, N. B.; Singh, K.; Harvey, T. (2024)
Digital terrain data, Image data, LiDAR point cloud, Elevation model, Uncompressed and Compressed